Enhancing Educational Interactions and Student Well-being through Blended Learning in Islamic Religious Education - Hanifah Atmi Nurmala; Humairourrohmah binti Mastor (LP3M IAI Al Urwatul Wutsqo Jombang, 2026)
This study aims to analyze the implementation of blended learning in Islamic Religious Education (PAI) to foster educational interaction and enhance students’ well-being at SMA Negeri Ploso Jombang. The rapid development of digital technology in education requires innovative learning models that not only utilize technology effectively but also maintain meaningful pedagogical relationships between teachers and students. This research employed a qualitative approach using a field research design. The research participants consisted of Islamic Religious Education teachers and twelfth-grade students at SMA Negeri Ploso Jombang. Data were collected through observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion, while data validity was ensured through triangulation. The findings reveal that the implementation of blended learning strengthens instructional interaction between teachers and students by integrating online and face-to-face learning activities. This learning model provides students with opportunities to study independently through digital media, thereby allowing classroom time to be devoted to discussions and value reflections. Furthermore, blended learning contributes to improved student well-being, as reflected in increased student engagement, more positive social relationships between teachers and students, and a more comfortable learning environment. These findings indicate that blended learning can serve as an effective pedagogical approach for integrating the use of technology with character development in Islamic Religious Education.